Technology absorption in indian industry / edited by Ashok V. Desai - Desai, Ashok V. (ed.) (New Delhi, 1988)
In Indian industrial economics, paradigms took root in the six ties whose influence on policy turned India's industrial perfor mance into one of the worst among the developing countries. Readers of this book will probably need no education in the paradigms: monopoly houses, multinationals, merchant capital, lack of demand-an entire generation of economists has been raised on this folklore of parochialism. The projects which led to the papers that follow had no intention of questioning this fairy tale; they just ran smack into it. It all started with the ICRIER-NCAER project on technology development; the idea of that project, which began in 1980, was first of all to repeat the 1968 NCAER survey of technical collaborations and com pare results after an interval of 13 years, and then to study in some detail the development of technology in a few industries. In the course of these industrial studies we formed a strong im pression that the picture of technology flows being dominated by monopolies or multinationals was seriously deficient; in fact, the market structure of technology supplies from abroad varied considerably from industry to industry, and it seemed to have an influence on the performance of the industry in India.
Keywords: Industry and State India